2020
DOI: 10.3102/0002831220905580
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Merit Pay: A Meta-Analysis

Abstract: Empirical research investigating the association between teacher pay incentives and student test scores has grown rapidly over the past decade. To integrate the findings from these studies and help inform the debate over teacher merit pay, this meta-analysis synthesizes effect sizes across 37 primary studies, 26 of which were conducted in the United States. Among the U.S. based studies, the results suggest that the effect of teacher merit pay on student test scores is positive and statistically significant (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 97 publications
2
26
0
Order By: Relevance
“…We based our method‐specific approach on the Cochrane Collaborative's tool for assessing risk of bias (Higgins & Altman, 2008, Higgins et al, 2011) and L. D. Pham et al's (2021) recent teacher merit‐pay meta‐analysis. Then, we gave a rating of “high risk” or “low risk” to each study, within four domains.…”
Section: Methodsmentioning
confidence: 99%
“…We based our method‐specific approach on the Cochrane Collaborative's tool for assessing risk of bias (Higgins & Altman, 2008, Higgins et al, 2011) and L. D. Pham et al's (2021) recent teacher merit‐pay meta‐analysis. Then, we gave a rating of “high risk” or “low risk” to each study, within four domains.…”
Section: Methodsmentioning
confidence: 99%
“…Merit pay for higher performing teachers is an idea that takes advantage of this concept. This is a very controversial approach, and studies performing on the practice have shown mixed results (Pham et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…• Inform decisions to sanction teachers that continually under-perform by either removing them from teaching duties or even terminating their service. In support, the theories of personnel economics postulate that compensation can inspire the workers to improve their practice, thereby boosting organisational performance and at the same time luring and retaining high performers while on the other hand, discouraging underperformers from either entering or staying in the system (Pham, Nguyen & Springer, 2017). Likewise, Muralidharan & Sundararaman (2011) also posit that linking a part of teachers' pay to objective measures of performance is popular with teachers.…”
Section: The Teacher Accountability Functionmentioning
confidence: 99%